Archives and Health program for dementia: A pilot study of a non-pharmacological creative arts-based intervention protocol - Sara Uboldi; Lorenza Iannacci; Vanda Menon; Alessandro Bortolotti; Giulia Candeloro; Alessandro Crociata; Valeria Pica; Angelo Romagnoli; Maria Tartari; Andrea Fabbo; Alessandra Marasco; Pier Luigi Sacco (Archives of Gerontology and Geriatrics Plus)
Introduction: The global rise in dementia prevalence necessitates innovative non-pharmacological interventions to enhance cognitive function and the quality of life of affected individuals. This pilot study evaluates the ''Archives and Health'' program, a creative arts-based initiative that uses archival materials to facilitate reminiscence therapy for individuals with dementia. Methods: This mixed-methods study involved a total of 50 participants (aged 65-94), divided into three different activities, with varying levels of cognitive impairment, recruited from different care settings. The program featured three interventions: ''Memory Box,'' ''My Memory Box,'' and the ''Pre-Texts Protocol,'' incorporating music to enhance personal engagement. Quantitative emotional well-being was assessed using the RADAR toolkit, while qualitative insights were derived from focus groups, interviews, and ethnographic observations Results: The ''My Memory Box'' intervention led to a significant decrease in negative affect (Mean pre = 8.73, Mean post = 7.00, p = 0.007) without altering positive affect. Conversely, the ''Pre-Texts Protocol'' exhibited consistent increases in positive affect across sessions (p-values ranging from 0.0001 to 0.0023). Qualitative analyses indicated that the program effectively activated autobiographical memories, improved social interactions, and fostered emotional resonance through multisensory engagement, particularly via music. Participants expressed enhanced social connectivity and personal relevance during activities.The results should be considered preliminary also in light of the mixed qualitative design evaluation, specifically chosen and studied by the researchers as a methodological reflection on the development of mixed qualitative methodologies. Discussion: The ''Archives and Health'' program demonstrated potential in improving emotional and social well-being among individuals with dementia. Its ability to evoke positive emotional responses and decrease negative states indicates the utility of archival materials and creative engagement in therapeutic contexts. Future studies with larger samples are necessary to confirm these findings and explore their clinical implications more robustly.